Formulation and In vitro Evaluation of Eudragit RL 100 Loaded Fexofenadine HCl Microspheres (Bangladesh Pharmaceutical Journal, 2016)
The present study deals with the formulation and evaluation of Fexofenadine hydrochloride (HCl) loaded sustained release microspheres by emulsion solvent evaporation method with Eudragit RL 100. The effects of percent drug loading on drug encapsulation efficiency, drug content and drug release rate were assessed. In vitro dissolution study was performed spectrophotometrically according to USP paddle method using phosphate buffer (pH 6.8) for 10 hours. The release rate of Fexofenadine HCl from the microspheres was significantly increased with the increase of drug loading. The drug release patterns were simulated in different kinetic orders such as zero order release kinetics, first order release kinetics, Higuchi release kinetics, Korsmeyer-Peppas release kinetics and Hixson-Crowell release kinetics to assess the release mechanism and Higuchi release kinetics was found to be the predominant release mechanism. Morphological changes due to different drug loading were assessed by scanning electron microscopic (SEM) technique. Differential scanning calorimetry and fourier transform infra-red (FT-IR) spectroscopy was performed to evaluate compatibility of drug with the polymer. A statistically significant variation indrug encapsulation efficiency and release rate was observed for variation in drug loading.Bangladesh Pharmaceutical Journal 19(1): 58-67, 2016